MANAJEMEN PEMBINAAN KESANTUNAN BERBAHASA DALAM PEMBELAJARAN PAI DI ERA REVOLUSI INDUSTRI 4.0 - Meity Wildanun Nasution; Sofyan Sauri; Ahmad Sukandar (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2021)
This study aims to reveal the management of language politeness coaching through learning Islamic Religious Education at Creative Junior High School (SMP) IHAQI Boarding School Bandung. The approach used in this research is a qualitative approach with descriptive methods. The data collection technique was done by triangulation; structured interview techniques with principals, vice principals, educators and students. Participatory observation techniques are carried out in activities and student financing programs. Documentation techniques by taking document or photo data related to student coaching activities. The results showed that; First, planning language politeness development through Islamic religious education learning at IHAQI Boarding School Bandung Creative Junior High School is done by compiling syllabus, lesson plans and journals, selecting suitable material / content and learning activities. Second, the implementation of language politeness development through Islamic religious education learning at IHAQI Boarding School Bandung Creative Junior High School is carried out directly by educators and deputy principals of student affairs. Third, evaluation of language politeness fostering through Islamic religious education learning at Ihaqi Creative Middle School in Bandung, namely the lack of development of polite speaking skills in students and it is felt that the method of politeness is ineffective when applied when learning online, so it needs proper formulation and more innovative language politeness exemplified in short learning time, especially in the PAI learning process.